The Role of Educational Unit Companions to Increase Transparency and Accountability in the Governance of BOS Funds - H. Soro , Suharyanto; Ningarumsari , Rike Junia; Rahmah, Suqya (Civiliza Publishing, Indonesia., 2025)
Transparency and accountability are one of the important issues and problems in the management of School Operational Assistance Funds (BOS). School operational assistance funds are used to support the creation of effective and superior schools. This study aims to find and analyze the role of Education Unit Companions (PSP) in improving the governance of BOS Funds in Paseh District, Bandung Regency. The approach used is a case study with triangulation techniques through observation, in-depth interviews, and documentation. The results of the study indicate that PSP has a strategic role in five main stages, namely: identification of needs, planning assistance, implementation of assistance, evaluation and reflection, as well as reporting and follow-up. The role of PSP can improve school compliance with regulations, strengthen accountability and encourage participation of education stakeholders. The conclusion of this study is that the assistance policy can be an effective tool in reforming education financial governance at the local level.